Inflammation and neurohormonal activation is increased at hospital admission in patients with ST-elevation myocardial infarction with diabetes compared to non-diabetic patients. (26th April 2021) - Kunkel, JB; Hassager, C; Moeller, JE; Holmvang, L; Jensen, LO; Frydland, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Rigshospitalets Forskningsfond. The Lundbeck Foundation. Background: Patients with diabetes have an increased risk of coronary artery disease (CAD). In patients with myocardial infarction (MI), diabetes is associated with a poor outcome. Inflammation and neurohormonal activation have previously been shown to be associated with poor outcomes in patients with ST-elevation MI (STEMI). We therefore sought to assess whether STEMI-patients with diabetes (DM) had increased levels of inflammation and neurohormonal activation upon hospital admission. Methods: In 1892 consecutive STEMI-patients from two danish tertiary heart centres, biomarkers reflecting neurohormonal activation (pro-atrial natriuretic peptide (proANP) and mid-regional pro-adrenomedullin (MRproADM)) and inflammation (soluble suppression of tumorigenicity 2 (sST2) and C-reactive peptide (CRP)) were measured upon admission before angiography. Patients were stratified according to DM or not. Results: In total, 245 (13%) patients had DM. DM patients were older (mean (SD) 66 (11) vs 63 (13) years old, p = 0.0002), had more comorbidities (hypertension, previous stroke/TIA, ischemic heart disease (IHD), chronic kidney dysfunction (CKD)), and higher body mass index (BMI). In addition, DM patients had a longer time from symptom debut to angiography and more often multivessel disease (MVD). We found no difference in admission troponin plasma concentrations. Upon hospital admission, DM patients had higher concentrations of MRproADM (median (IQR) 0.88 (0.64-1.20) vs. 0.71 (0.58-0.90) nmol/L, p < 0.0001), sST2 (41 (64-31) vs. 39 (55-28) ng/ml, p = 0.01), and CRP (4.5 (1.9-12.1) vs. 3.4 (1.4-8.3) mg/L, p = 0.001) but not proANP (figure). When adjusted for age, BMI, CKD, IHD, time from symptom debut to angiography, and MVD, DM remained associated with increased MRproADM (OR (95% CI) 1.35 (1.05; 1.74), p = 0.02) and sST2 (1.20 (1.02; 1.41), p = 0.03), but no longer with CRP. Patients with DM had a higher one-year all-cause mortality rate (12% vs. 9.4%, p = 0.03). Conclusion: STEMI patients with diabetes have increased neurohormonal activation and inflammation at hospital admission compared to patients without diabetes. This may play a role in the increased mortality in STEMI patients with diabetes.